The Analysis of Lexical Cohesion in The Global Story Podcasts by BBC World Service YouTube Channel - Khorina, Mulyati; Rasis, Vanessa Mutiara; Komarawan, Yulizar; Firdhani, Anggi Rizky (Jurusan Bahasa Inggris - Politeknik Negeri Bandung, 2025)
Lexical cohesion can be found in both written and spoken texts. It is critical because it is a device to make text cohesive and coherent. Consequently, lexical cohesion serves as an indicator to measure whether a text is cohesive or coherent. However, using lexical cohesion appropriately is challenging, especially for non-native English learners. Therefore, the purpose of this article was to analyze lexical cohesion found in spoken text. This study applied qualitative method and the data were collected from five podcasts of The Global Story podcast by the BBC World Service YouTube channel. In analyzing the data, the theory of lexical cohesion proposed by Paltridge (2022) was applied. The results reveal that all types of lexical cohesion, such as repetition, synonymy, antonymy, hyponymy, meronymy, and collocation are found in the data. Among them, collocation is the most frequently used. Moreover, lexical cohesion in podcasts shows its essential role in maintaining coherence and facilitating comprehension in spoken text. These findings can be used as the reference for improving the vocabulary of non-native English learners, especially for spoken use.